Toxic Effects of Cd and Zn on the Photosynthetic Apparatus of the Arabidopsis halleri and Arabidopsis arenosa Pseudo-Metallophytes - Szopiński, Michał; Sitko, Krzysztof; Gieroń, Żaneta; Rusinowski, Szymon; Corso, Massimiliano; Hermans, Christian; Verbruggen, Nathalie; Małkowski, Eugeniusz (Frontiers in Plant Science, 2019)
Hyperaccumulation and hypertolerance of Trace Metal Elements (TME) like Cd and Zn are highly variable in pseudo-metallophytes species. In this study we compared the impact of high Cd or Zn concentration on the photosynthetic apparatus of the Arabidopsis arenosa and Arabidopsis halleri pseudo-metallophytes growing on the same contaminated site in Piekary Slaskie in southern Poland. Plants were grown in hydroponic culture for 6 weeks, and then treated with 1.0 mM Cd or 5.0 mM Zn for 5 days. Chlorophyll a fluorescence and pigment content were measured after 0, 1, 2, 3, 4, and 5 days in plants grown in control and exposed to Cd or Zn treatments. Moreover, the effect of TME excess on the level of oxidative stress and gas-exchange parameters were investigated. In both plant species, exposure to high Cd or Zn induced a decrease in chlorophyll and an increase in anthocyanin contents in leaves compared to the control condition. After 5 days Cd treatment, energy absorbance, trapped energy flux and the percentage of active reaction centers decreased in both species. However, the dissipated energy flux in the leaves of A. arenosa was smaller than in A. halleri. Zn treatment had more toxic effect than Cd on electron transport in A. halleri compared with A. arenosa. A. arenosa plants treated with Zn excess did not react as strongly as in the Cd treatment and a decrease only in electron transport flux and percentage of active reaction centers compared with control was observed. The two species showed contrasting Cd and Zn accumulation. Cd concentration was almost 3-fold higher in A. arenosa leaves than in A. halleri. On the opposite, A. halleri leaves contained 3-fold higher Zn concentration than A. arenosa. In short, our results showed that the two Arabidopsis metallicolous populations are resistant to high Cd or Zn concentration, however, the photosynthetic apparatus responded differently to the toxic effects.